A centralized approach to out‐of‐province genetic testing leads to cost savings: the Alberta experience. (4th January 2013) - Lilley, M; Christian, S; Blumenschein, P; Chan, S; Somerville, M
Abstract : The Genetic Resource Center (GRC) is a centralized process for requesting genetic testing that is not available within the province (Alberta, Canada). In order to assess potential cost savings associated with this process, all applications received by the GRC in 2010 were reviewed, and cost savings were recorded for statistical analysis. Seven areas of cost savings were identified: (i) negotiated pricing, (ii) laboratory selection, (iii) testing setup in‐province, (iv) duplicate testing, (v) inappropriate testing, (vi) sequential testing and (vii) testing offered within the province.The total test cost of the 615 applications submitted in 2010 without the GRC process would have been $766, 783 (Canadian dollars). A total cost savings of $112, 201 was achieved through the GRC, which represents 15% of the total cost of requested testing ($112, 201/$766, 783). This is the first study to examine areas of cost savings for genetic testing sent out‐of‐province. The greatest cost savings resulted from the areas of laboratory selection and negotiated pricing. A centralized process to manage out‐of‐province genetic test requests results in consistency in testing and significant cost savings.